Co-occurrence Pattern of Posttraumatic Stress Disorder and Depression in People Living With HIV: A Latent Profile Analysis - Meng, Jingjing; Tang, Chulei; Xiao, Xueling; Välimäki, Maritta; Wang, Honghong (Frontiers in Psychology, 2021)
Background: The comorbidity of posttraumatic stress disorder (PTSD) and depression is common among people living with the human immunodeficiency virus (PLWH). Given the high prevalence and serious clinical consequences of the comorbidity of these two disorders, we conducted a latent profile analysis to examine the co-occurrence pattern of PTSD and depression in PLWH. Methods: The data for this cross-sectional study of PLWH were collected from 602 patients with human immunodeficiency virus (HIV) in China. A secondary analysis using latent profile analysis was conducted to examine HIV-related PTSD and depression symptoms. Results: A four-class solution fits the data best, with the four classes characterized as asymptomatic (42.9%), mild symptoms (33.9%), low to moderate symptoms (19.8%), and high to moderate symptoms (3.4%). The severity of PTSD and depression symptoms were comparable in this solution, and no group was dominated by PTSD or depression. Conclusions: The absence of a distinct subcluster of PLWH with only PTSD or depression symptoms supports that PTSD and depression in PLWH are psychopathological manifestations after traumatic exposures. Health care staff should pay more attention to the existence of comorbid symptoms of individuals, develop integrated interventions for the symptoms cluster, and evaluate their effectiveness in clinical practice.